¿Abalorios de calzado romano en Augusta Emerita? - Macarena Bustamante Álvarez; Ana María Bejarano Osorio (Mélanges de la Casa de Velázquez, 2018)
Presented here is a burial deposit located in a part of the necropolis of the ancient capital of Lusitania, August Emerita (Mérida, Badajoz province). A contextual and stratigraphic study of the dig has made it possible to date the find in the first century CE. There, in addition to ceramic and metal objects, there was a pair of phytomorphic adornments in mother-of-pearl which we associated with the «eccentric» ornamentation that was developed for footwear in ancient times. In addition to a comprehensive analysis of the find, we took the opportunity to address the question of ancient shoemaking from an archaeological perspective. To that end, as well as running a search for parallels on the items, an iconographic analysis was performed on the larger figures, and textual sources on footwear and adornments therefor were examined.